A new and the second fossil species of the genus Ephedrus Haliday, 1833(Hymenoptera: Braconidae: Aphidiinae) from Baltic amber - Davidian, Elena M.; Manukyan, Andranik R.; Belokobylskij, Sergey A. (Zootaxa, 2023)
A new species of aphid parasitoid, Ephedrus carsteni Davidian, sp. nov. (Braconidae: Aphidiinae), is described and illustrated from Late Eocene Baltic amber. This new species was compared with the fossil Ephedrus mirabilis Timon-David, 1944 (Oligocene imprint from Bassin de Marseille), E. primordialis Brues, 1933 (Eocene Baltic amber) and E. rasnitsyni Davidian & Kaliuzhna, 2021 (Eocene Sakhalinian amber), as well as with the extant E. validus (Haliday, 1833) and E. carinatus Tomanović, 2020.